Antimycobacterial Activity of Salicylanilide Benzenesulfonates - Jiřina Stolaříková; Jarmila Vinšová; Martin Krátký; Nabila Guisado Rodriguez (Molecules, 2012)
A series of eighteen novel esters of salicylanilides with benzenesulfonic acid were designed, synthesized and characterized by IR, 1H-NMR and 13C-NMR. They were evaluated in vitro as potential antimycobacterial agents towards Mycobacterium tuberculosis, Mycobacterium avium and two strains of Mycobacterium kansasii. In general, the minimum inhibitory concentrations range from 1 to 500 µmol/L. The most active compound against M. tuberculosis was 4-chloro-2-(4-(trifluoromethyl)phenylcarbamoyl)-phenyl benzenesulfonate, with MIC of 1 µmol/L and towards M. kansasii its isomer 5-chloro-2-(4-(trifluoromethyl)phenylcarbamoyl)phenyl benzenesulfonate (MIC of 2–4 µmol/L). M. avium was the less susceptible strain. However, generally, salicylanilide benzenesulfonates did not surpass the activity of other salicylanilide esters with carboxylic acids.